Management of water resources in companies located in the Industrial District of Itabira – MG (Research, Society and Development, 2019)
The Industrial District of the municipality of Itabira (MG) is in the Candidópolis Stream watershed, a source of raw water for the Purity System, responsible for supplying a large part of the city's population. Thus, this article aimed to analyze the effluent management in four companies located in the Industrial District and the relevance of this process for the protection of water resources in the Candidópolis Stream microbasin. Data collection was based on documents such as Environmental Licensing, Environmental Control Report, Environmental Control Plan, Environmental Impact Study of companies from different segments such as slaughter of small animals, textile, steel, concrete production. According to the results obtained, all the analyzed companies present, according to Normative Resolution n° 217/2017 of the State Environmental Policy Council (COPAM), a polluting/degradable potential classified as medium to large, which may have impacts on water supply, raising costs for the treatment of this, in case the effluents from these projects are launched in a receiving body without the correct treatment. It was verified that one of the companies has in its unit Effluent Treatment Station, while the others recycle the effluent in the processes. It should be emphasized that the search for sustainable alternatives to meet the demands for water resources of the enterprises is necessary, such as reuse of treated effluent and rainwater harvesting. In this scenario, managing and treating industrial effluents is extremely important for the protection of receiving bodies, however, it is essential to have an overall view of this management tool.